Friction stir processing of a high entropy alloy Fe42Co10Cr15Mn28Si5 with transformative characteristics: Microstructure and mechanical properties. (September 2021) - Sittiho, Anumat; Bhattacharyya, Madhumanti; Graves, Jadzia; Nene, Saurabh S.; Mishra, Rajiv S.; Charit, Indrajit
Abstract: High entropy alloys (HEA) are an emerging class of novel metallic alloys with the ability to develop unique microstructural modification by using thermomechanical processing techniques. In this study, friction sir processing (FSP), widely regarded as an effective thermomechanical processing technique, was applied to a rolled HEA of nominal composition Fe42 Co10 Cr15 Mn28 Si5 (at%). The work involves examination and analysis of the microstructural characteristics by optical microscopy, transmission electron microscopy and electron backscatter diffraction. Also, X-ray diffraction was used to identify the different phases present in the HEA both before and after FSP. The mechanical behavior of the HEA was evaluated by compression testing at room temperature. The compressive yield stress of the base metal changed from 277 MPa to about 270 MPa although statistically no appreciable change was noted. The work hardenability of the SZ and the parent material was analyzed in terms of strain hardening exponents and strain hardening rates in the light of existing work hardening theories.